Prozesstechnische Untersuchungen zum Rührreibschweißen metallischer Werkstoffe - Giera, Artur (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2008)
The presented work exhibits friction stir welding as an innovative welding technique for similar and dissimilar materials as steel and aluminium in sheet thicknesses of about 1 mm. By welding in the solid phase hot cracks, inclusions or blowholes are completely avoided. This enables on the one hand high quality assemblies regarding the technical requirements and on the other hand cost efficient the assemblies as subsequent machining is unnecessar